Injury, disability and quality of life after the 2009 earthquake in Padang, Indonesia: a prospective cohort study of adult survivors - Sudaryo, Mondastri K.; Phalkey, Revati; Marx, Michael (Global health action, 2012)
BackgroundOn 30 September 2009, a 7.6 magnitude earthquake severely hit the coast of Padang city in West Sumatra, Indonesia leaving about 1,117 people dead and injuring another 3,515. Health consequences such as physical injury, co-morbidity, disability and quality of life over time are seldom reported among survivors after earthquakes.ObjectivesTo investigate the associations between injury, disability and quality of life amongst adult survivors in Padang city after the 2009 earthquake.Design/MethodsA prospective cohort study was conducted to compare adult injured (184) and adult non-injured (93) subjects over a 6-month period. Data on physical injury, co-morbidities, disability and quality of life were collected through interviews and measured quantitatively in three phases, i.e. at baseline, end of 3 and 6 months.ResultsDisability scores were consistently and significantly higher among injured subjects compared to non-injured, even when adjusted for co-morbidities (i.e. acute symptoms and chronic diseases). The highest disability score amongst injured subjects was attributed to ‘feeling discomfort/pain’. Quality of life attribute (QLA) scores, were significantly lower amongst injured people as compared to those non-injured even when adjusted for co-morbidities. The lowest QLA item score amongst the injured was ‘pain, depression and anxiety’. Significant and consistent negative correlations were found between disability and QLA scores in both the injured and non-injured groups.ConclusionPhysical injury is significantly correlated with both higher disability and lower quality of life, while disability has significant negative correlation with quality of life. The findings suggest that, through disability, injury may contribute to decreased quality of life. It is therefore recommended to promptly and adequately treat injuries after disasters to prevent any potential for disability and hence restore quality of life.